1990
DOI: 10.1161/01.cir.81.5.1575
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery imaging with intravascular high-frequency ultrasound.

Abstract: Safe and effective clinical application of new interventional therapies may require more precise imaging of atherosclerotic coronary arteries. To determine the reliability of catheter-based intravascular ultrasound as an imaging modality, a miniaturized prototype ultrasound system(1-mm transducer; center frequency, 25 MHz) was used to acquire two-dimensional, crosssectional images in 21 human coronary arteries from 13 patients studied at necropsy who had moderate-to-severe atherosclerosis. Fifty-four atheroscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
154
1
9

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(173 citation statements)
references
References 30 publications
8
154
1
9
Order By: Relevance
“…MRI and intravascular ultrasound are promising technologies for directly imaging plaque morphology. 7,8 For the evaluation of dynamic mechanics, arterial elasticity has been determined by measuring the pulse wave velocity 9 and rough change in the diameter of the artery. 10,11 However, a method to detect the vulnerability of atherosclerotic plaque with sufficient accuracy has not yet been reported.…”
mentioning
confidence: 99%
“…MRI and intravascular ultrasound are promising technologies for directly imaging plaque morphology. 7,8 For the evaluation of dynamic mechanics, arterial elasticity has been determined by measuring the pulse wave velocity 9 and rough change in the diameter of the artery. 10,11 However, a method to detect the vulnerability of atherosclerotic plaque with sufficient accuracy has not yet been reported.…”
mentioning
confidence: 99%
“…Several studies have shown excellent correlations between the lumen cross-sectional area measured from ul- trasound images compared with direct measurements from histologic cross-sections [1,5,6,8,9]. In addition, an in vitro study using acrylamide casts of a phantom model has demonstrated that contrast angiography overestimates the true lumen cross-sectional area compared with intravascular ultrasound when the lumen is not elliptical but irregular experienced interventional angiographers are impressed by the huge amount of residual atheroma that remains at the site of balloon angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…O seu limite interno, isto é, a transição entre a camada média e a adventícia, é bem visível ao ultra-som, sendo denominada membrana elástica externa. Entretanto, os limites externos da adventícia são imprecisos ao ultrasom, pois os tecidos periadventiciais se confundem com os da adventícia, por apresentar em quantidades semelhantes de colágeno e elastina 5,[8][9][10] .…”
Section: -Interpretação Do Ultra-som Intracoronarianounclassified
“…O ultra-som intracoronariano é uma técnica tomográfi-ca que permite o estudo in vivo da parede vascular normal, dos componentes da placa aterosclerótica e das caracterís-ticas quantitativas e qualitativas envolvidas no ateroma 1,5 . No campo da pesquisa, o ultra-som intracoronariano trouxe contribuições incontestes para o melhor conhecimento da doença aterosclerótica e do fenômeno da reestenose após a realização de intervenção coronariana percutânea 6 .…”
Section: -Introduçãounclassified